Pathophysiology of the Venous Thromboembolism Risk in Preeclampsia - Kelliher, Sarah; Maguire, Patricia B.; Szklanna, Paulina B.; Weiss, Luisa; Ewins, Karl; O'Doherty, Roseann; Angelov, Daniel; Ní Áinle, Fionnuala; Kevane, Barry (Hämostaseologie, 2020)
Preeclampsia complicates up to 8% of pregnancies and is a leading cause of fetomaternal morbidity andmortality. Treatment options are limited, with supportive care and delivery of the placenta representing the cornerstone of current management strategies. Derangements in blood coagulation are wellrecognised in this disorder and appear to favour an increased risk of venous thromboembolism among affected women. This risk appears to be most significant in the postpartum period. The mechanisms underlying this increased thrombosis risk remain to be fully elucidated although increased expression of procoagulant factors, endothelial dysfunction, attenuation of endogenous anticoagulant activity and increased platelet activity have been implicated in the prothrombotic tendency. Preeclampsia is also occasionally complicated by life-threatening haemorrhagic events and current evidence suggests that in some severe manifestations of this disease a coagulopathy with a clinical bleeding tendency may be the predominant haemostatic abnormality. Identifying affected women at significant risk of thrombosis and managing the competing thrombotic and haemorrhagic risks continue to be a significant clinical challenge. Derangements in blood coagulation are also implicated in the pathogenesis of preeclampsia; however, the role of antiplatelet or anticoagulant drugs in the prevention and treatment of this disorder remains a source of considerable debate. In addition, the potential role of specific haemostatic markers as diagnostic or screening tools for preeclampsia has also yet to be determined. Further characterisation of the underlying molecular mechanisms would likely be of major translational relevance and could provide insights into the pathogenesis of this disease as well as the associated haemostatic dysfunction.
Keywords: thrombosis; pregnancy; haemostasis